An ethnographic perspective on traditional pig rearing practices among major communities of Dhemaji district, Assam - Pathak, Dr. Prajwalita; Gogoi, Gunjan (The Indian Journal of Animal Sciences, 2026)
Pig rearing constitutes a vital component of livelihood and cultural identity in Northeast India, particularly in flood-prone districts like Dhemaji of Assam. This study was undertaken to document and analyze traditional pig husbandry practices across six major ethnic communities namely Mising, Deori, Sonowal Kachari, Hajong, Boro, and Ahom. Using participatory rural appraisal, focus group discussions, and structured interviews with 180 farmers, information wear collected on indigenous practices of housing, feeding, and ethno-veterinary healthcare. Results revealed a wide range of context-specific strategies/ practices that were low-cost, eco-friendly, and well-adapted to the flood-prone agro-ecology. Bamboo-walled pens with thatched roofs (86.67% adoption) and deep-litter systems using paddy straw (68.89%) were common housing practices. Feeding boiled tubers and other root crops (93.33%) and rice with kitchen leftovers (90.56%) dominated nutritional strategies, supplemented with banana pseudostem and traditional fermented rice-beer dregs. Ethno-veterinary practices were diverse, with 24 medicinal plant species identified, including Lasia spinosa for dysentery (97.22% adoption) and Mikania micrantha for piglet diarrhoea (89.44%). These practices demonstrated high perceived effectiveness, indicating their continued relevance under resource-limited and disaster-prone conditions. The findings highlight the significance of documenting Indigenous Technical Knowledge (ITK) to preserve cultural heritage, validate local innovations, and design location-specific interventions that integrate traditional wisdom with modern piggery management for sustainable rural livelihoods